1989
DOI: 10.1111/j.1365-277x.1989.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

A health education campaign to prevent osteomalacia in Asian women in Glasgow: 1984–86

Abstract: Vitamin D deficiency is common in Asian women in Britain. Self‐supplementation with vitamin D provides effective prophylaxis. Between 1984‐86 a Health Education campaign promoted vitamin D supplementation by Asian women in Glasgow. Vitamin D supplements were provided at cost‐price in Health Board clinics and a co‐ordinator and four Asian link‐workers promoted the aims of the campaign. Despite the campaign few Asian women presently purchase vitamin D supplements. Serum 25‐OHD and calcium concentrations were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…There have been few follow up reports following these preventative campaigns and although Dunnigan et al. (1985) reported some success with children there was a less favourable response in adult women (Henderson et al , 1989). Leicestershire Health Authority, although aware of the potential problems from early on, has not adopted any such policy in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few follow up reports following these preventative campaigns and although Dunnigan et al. (1985) reported some success with children there was a less favourable response in adult women (Henderson et al , 1989). Leicestershire Health Authority, although aware of the potential problems from early on, has not adopted any such policy in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, when vitamin D de®ciency was ®rst recognized as a problem in the Asian community various preventive policies were suggested; daily or annual supplementation (Stephens et al, 1981) and forti®cation of chapati¯our (Pietrek et al, 1976) with vitamin D. The Department of Health Working Party rejected the idea of forti®cation of other foods, though forti®cation of margarine was recommended (COMA, 1980) and is still retained (COMA, 1993). There have been few follow up reports following these preventative campaigns and although Dunnigan et al (1985) reported some success with children there was a less favourable response in adult women (Henderson et al, 1989). Leicestershire Health Authority, although aware of the potential problems from early on, has not adopted any such policy in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of free vitamin D supplements in 1979 in an effort to reduce the prevalence of Asian rickets in the city is not responsible for this trend (Dunnigan et al 1985). Supplement uptake declined rapidly within a few years of the onset of the campaign and vitamin D supplements are now rarely consumed by Asian schoolchildren and women (Henderson et at. 1989).…”
Section: Trends In the Prevalence Of Asian Rickets And Osteomalaciamentioning
confidence: 99%
“…In the UK, food is not routinely supplemented with vitamin D, although this has been successful in other countries. There was a successful supplementation programme using flour in Glasgow in the 1980s17 18; however, there is a need for robust data around modern dietary intake of children in the UK to inform an effective plan for food fortification.…”
Section: Discussionmentioning
confidence: 99%